Inovasi Penyisipan Karbon dari Pektin pada Pembuatan Membran Interlayer-free Silika-pektin - Amalia Enggar Pratiwi; Muthia Elma; Meilana Dharma Putra; Agus Mirwan; Aulia Rahma; Erdina Lulu Atika Rampun (Jurnal Kimia Sains dan Aplikasi, 2019)
Water scarcity is the main issues in Indonesia especially for coastal areas. As a consequence, the water has high salinity of >50.000 ppm salt concentration where an appropriate treatment is necessary before consumed. In this case, desalination process could be carried out using inorganic silica membranes. However, during the process the pore of silica membranes were collapsed due to the directly contact of pores to water molecules for a long term performance. Thereby, in this work the innovation of membrane fabrication using carbon templated in silica matrices has been successfully fabricated. Literally, the carbon templates could be improving the membrane hydro-stability. The interlayer-free silica-pectin membrane was fabricated using TEOS as silica precursor and carbon templated from pectin apple. All membranes waere calcined in variance temperature of 300 and 400°C via Rapid Thermal Processing (RTP). The FTIR results show some functionalization of siloxane, silanol and a new bond of silica-carbon. Whereas, the SEM images show the membrane morphology that the membrane not dense and crack-free with thin film's thickness of ~ 1 μm. An excellent condition of interlayer-free silica-pectin membrane was obtained at pectin concentration of 2.5 %wt. (300°C) and 0.5 %wt. (400°C) with highest functionalization of siloxane and silica-carbon bonds. The existence of silica-carbon bonds were capable to enhancing the membrane hydro-stability. In addition, the carbon chains were contributed to form a smaller pores but also robust pore structures. Those fabricated membranes were shown a good promising due to fast and low cost fabrication with high quality to applicate in seawater desalination.